In vitro Evaluation of Epiphytic Bacteria from Table Grapes for the Suppression of Botrytis cinerea - Ferreira, J.H.S. (South African Journal of Enology and Viticulture, 2017)
Epiphytic bacteria were isolated from leaves and bunches of Waltham Cross grapes and tested for their inhibition of Botrytis cineria. Trichoderma harzianum from grapevine wood was also evaluated. Eighty bacterial isolates inhibited germination of B. cinerea spores on potato dextrose agar. Sixteen of these isolates were tested in vitro for their efficacy againstB. cinerea rot on grape berries (cv. Waltham Cross). One bacterial isolate totally inhibitedB. cinerea whereas the efficacy of thirteen of the isolates, including T. harzianum, varied between 70,8 and 87,5%. lt was also demonstrated that certain fungicides exerted a negative effect on these bacterial isolates.